Ameliorating mechanism of nuciferine on high-fat diet-induced dyslipidemia and hepatic steatosis by regulating intestinal absorption and serum extracellular vesicles in rats. (August 2022) - Dong, Xiaochen; Zhu, Shengnan; Liu, Jun; Dong, Zonghua; Guan, Feng; Xu, Aichun; Zhao, Jin; Ge, Jian
Graphical abstract: Highlights: Nuciferine regulated lipid metabolism through PPARα-LXRα-ABCA1 signaling. Nuciferine ameliorated dyslipidemia by modulating miRNA signaling in serum EVs. Serum EV miRNAs interacted with the mRNAs of PPARα, ABCA1, and CYP7A1. Nuciferine improved hyperlipidemia by modulating NPC1L1 and ABCG5. Abstract: We investigated the effects of nuciferine rich in Lotus leaf on the amelioration of hepatic steatosis and dyslipidemia of hyperlipidemic rats, and explored the underlying mechanism on miRNAs and genes expression. Serum extracellular vesicles (EVs) from rats were prepared and characterized, and interactions between miRNAs and target mRNAs were validated in 293T cell line with the double luciferase reporter gene assay. Results showed that nuciferine significantly induced the expression of PPARα, ABCA1, CYP7A1, LXRα in liver and ABCG5 in intestine, while NPC1L1 expression was markedly reduced. In vitro, double luciferase reporter assays showed that miRNA-764-5p, miRNA-758-3p, and miRNA-126-5p interacted with the target mRNAs of PPARα, ABCA1, and CYP7A1, respectively. And the effect of nuciferine on lipid metabolism in rats was related to regulate intestinal absorption and serum EVs miRNAs. These miRNAs were able to reduce lipid levels by targeting lipid metabolism genes and up-regulating PPARα-LXRα-ABCA1 pathway and CYP7A1 expression.